Inter-relationships among key reproductive health indicators in sub-Saharan Africa focusing on the central role of maternal literacy. Issue 4 (13th February 2020) - Woldegiorgis, Mulu Abraha; Meyer, Denny; Hiller, Janet E; Mekonnen, Wubegzier; Bhowmik, Jahar
Abstract: Background: Indicators of reproductive health (RH) are expected to be both inter-related and associated with key social determinants. As the provision of RH services is usually integrated, the effort to improve one RH component should influence the other components. However, there is a lack of evidence-based models demonstrating the inter-relationships. The purpose of this study was to examine the inter-relationships among key RH indicators and their relationship with women's literacy in sub-Saharan Africa (SSA). Methods: Data were sourced from the most recent demographic and health survey conducted between 2010 and 2016 in 391 provinces of 29 SSA countries. We examined seven RH indicators along with women's literacy. The unit of analysis was at the provincial level. Structural equation modelling was used to examine the strength of relationships among these indicators and with women's literacy, using the total standardized effect sizes. Significance tests and 95% confidence intervals (CIs) for these effects were calculated using a bias-corrected bootstrap method. Results: RH indicators are strongly interrelated and are associated with women's literacy. The strongest relationship is observed between women's literacy rate and the contraception prevalence rate, with a total standardized effect size of 0.79 (95% CI 0.74–0.83). The model of inter-relationships developed in this study may guide the design, implementation and evaluation of RH policies and programmes. Conclusions: The key challenge in reducing fertility in SSA is to reduce people fertility desire. This could mainly be addressed by enhancing integrated approaches especially between the education and health sectors.